Mr icy-cold and other stories - Blyton, Enid (Award Worksop, 2007)
"Mr. Icy-Cold and Other Stories" is a collection of short tales that blend the fantastical with everyday life, often featuring quirky characters and imaginative plots. The title story, Mr. Icy-Cold, revolves around a mysterious man who brings a chilling atmosphere wherever he goes, with a hidden secret that changes the lives of those he encounters. The other stories in the collection explore themes of human nature, moral dilemmas, and whimsical, sometimes eerie, twists. Each narrative captures the reader's imagination with its blend of humor, suspense, and thought-provoking scenarios.